2008
DOI: 10.1212/01.wnl.0000285080.70324.27
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia is a protective factor in amyotrophic lateral sclerosis

Abstract: Hyperlipidemia is a significant prognostic factor for survival of patients with amyotrophic lateral sclerosis. This finding highlights the importance of nutritional intervention strategies on disease progression and claims our attention when treating these patients with lipid-lowering drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
384
6
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(429 citation statements)
references
References 26 publications
31
384
6
8
Order By: Relevance
“…Furthermore, with the limitation period between 25-35% of total energy intake, and nutritional recommendations dont involve replacing dairy products by skimmed and whole decrease in consumption of food of animal origin. Dupuis et al 46 observed that dyslipidemia plays a protective factor for disease progression over 12 months in the survival of such patients. Suggested treatments to control dyslipidemia may meddle in ALS progression.…”
Section: Important Clinical Characteristicsmentioning
confidence: 99%
“…Furthermore, with the limitation period between 25-35% of total energy intake, and nutritional recommendations dont involve replacing dairy products by skimmed and whole decrease in consumption of food of animal origin. Dupuis et al 46 observed that dyslipidemia plays a protective factor for disease progression over 12 months in the survival of such patients. Suggested treatments to control dyslipidemia may meddle in ALS progression.…”
Section: Important Clinical Characteristicsmentioning
confidence: 99%
“…Furthermore, SOD1 G93A and SOD1 G86R mice show a decrease in body weight and fat mass during disease progression, reduced levels of circulating triglycerides, and evidence of increased lipolysis (Dodge et al 2013, Kim et al 2011a, Fergani et al 2007, Dupuis et al 2004. ALS patients also exhibit higher resting levels of energy expenditure, weight loss, a hypermetabolic phenotype and increased lipolysis (Kasarskis et al 1996, Desport et al 2005, Dupuis et al 2008, Bouteloup et al 2009, Funalot et al 2009, Dodge et al 2013. Hence, there is growing evidence for decreased glucose utilisation and metabolic re-programming in…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism was described as deeply involved in ALS pathophysiology [52,53]. In particular, several studies reported hyperlipidemia in patients with ALS [53][54][55][56][57], with a potential link with patient survival [53].…”
Section: Moderate Effect On Metabolismmentioning
confidence: 99%